On C^*-algebra generated by Fock representation of Wick algebra with braided coefficients - Proskurin, D. P. (Methods of Functional Analysis and Topology, 2011)
We consider C^*-algebras W(T) generated by operators of Fock representations of Wick *-algebras with a braided coefficient operator T. It is shown that for any braided T with ||T||